Peramalan Jumlah Produksi Tebu Menggunakan Metode Time Series Model Moving Averages - Nabila Azahra; Salsabila Cahya Alifia; Nevandra Putra Andyka; Sena Wijayanto; M Yoka Fathoni (JURIKOM (Jurnal Riset Komputer), 2022)
Plantation is all activities that use certain and specific plants with soil or other parts of plants in adapted ecosystems. Other plantation activities also include processing and marketing of these crops. In the plantation sub-sector, sugar cane is an important plantation and national economic development strategy and contributes significantly to the plantation sub-sector. Sugarcane is a plantation crop that is widely grown in Indonesia, such as in Java, North and South Sumatra. One of the sugarcane producing areas in Purworejo Regency is Loano District. There are many sugar factories scattered throughout the sugar cane development area and the leading sugarcane plants are in Purworejo Regency. The purpose of this research is to predict production to meet market demand using the Time Series method with the Moving Average model. This study uses a Moving Average model consisting of: Single Moving Average (SMA) and Weighted Moving Average (WMA) with forecasting accuracy using Mean Square Error (MSE) and Mean Absolute Error (MAE) as the selection of the best model to be used for forecasting. From this study, the results of forecasting the amount of sugarcane production in Loano District for the next 4 periods, after 2015 from the WMA model, are: 113,91 ton; 135,62 ton; 101,96 ton; and 89,88 ton. The best model result is the Weighted Moving Average (WMA) model with the smallest forecasting accuracy value, namely the MSE value of 1.833,07 and the MAE of 36,07.